A robust approach to pore pressure prediction applying petrophysical log data aided by machine learning techniques; Energy Reports; Vol. 8 - Zhang Guodao; Davoodi Sh. Shadfar; Shamshirband Shahab; Ghorbani Hamzeh; Mosavi Amir; Moslehpour Massoud (2022, 2022)
Title screen